EPC Minutes 2005-04-14 - Academic Senate:::::::::
Educational Policies Committee. Special Student Report. Approval of Agenda – Approved. Approval of Minutes of 12/10/2020 – Approved. Chair Report. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Consent items: From EPC: Proposal for the Environmental Science, Geography and Management BS, as well as the Geography and Planning BA programs (and all associated course proposals and discontinuances) and From EPC: Proposal for elevation to full degree of the MA in Educational Leadership and associated discontinuance of the MA in Education with Concentration in Educational Leadership – Approved. Upcoming WASC visit. Associated Student Report. Statewide Senators Report. Staff Representative Report. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report.